La danza como herramienta para la inclusión educativa en los niños de 4 a 5 años de la Unidad Educativa 2 de Agosto de la provincia de Pichincha cantón Mejía, de la parroquia Cutuglagua durante el período lectivo 2014 – 2015 - Tapia Ortiz, Hilda Salome (2015)
This work is based on the need for dance activities as there children / as difficulties in socializing adapt, in order to foster a help to solve existing problems and seek solutions in the classroom of the Educational Unit August 2 Canton Mejia Pichincha province for school year 2014-2015. As the year progresses teacher training to acquire new methodologies and getting the skills, abilities in dance activities that facilitate the teaching-learning process in the motor development. This will allow the implementation of activities to help children fully formed to stimulate their creativity and imagination .To develop research was supported in the literature sources, field. Techniques for obtaining the information are: The observation record the interview survey, the list of processions....